Evaluation of the novel sepsis biomarker host-derived delta-like canonical notch Ligand 1 - a secondary analysis of 405 patients suffering from inflammatory or infectious diseases - Hölle, Tobias; Rehn, Patrick; Leventogiannis, Konstantinos; Kotsaki, Antigone; Kanni, Theodora; Antonakos, Nikolaos; Psarrakis, Christos; Damoraki, Georgia; Schenz, Judith; Schmitt, Felix; Uhle, Florian; Weigand, Markus A.; et al. (International journal of molecular sciences, 2023)
Sepsis is defined as organ failure caused by dysregulated host response to infection. While early antibiotic treatment in patients with acute infection is essential, treating non-infectious patients must be avoided. Current guidelines recommend procalcitonin (PCT) to guide discontinuation of antibiotic treatment. For initiation of therapy, there is currently no recommended biomarker. In this study, we evaluated Host-Derived Delta-like Canonical Notch Ligand 1 (DLL1), a monocyte membrane ligand that has shown promising results in differentiating infectious from non-infectious critically ill patients. Soluble DLL1 levels were measured in plasma samples of six different cohorts. The six cohorts comprise two cohorts with non-infectious inflammatory auto-immune diseases (Hidradenitis Suppurativa, Inflammatory Bowel Disease), one cohort of bacterial skin infection, and three cohorts of suspected systemic infection or sepsis. In total, soluble DLL1 plasma levels of 405 patients were analyzed. Patients were divided into three groups: inflammatory disease, infection, and sepsis (defined according to the Sepsis-3 definition), followed by the evaluation of its diagnostic performance via Area Under the Receiver Operating Characteristics (AUROC) analyses. Patients of the sepsis group showed significantly elevated plasma DLL1 levels compared to patients with uncomplicated infections and sterile inflammation. However, patients with infections had significantly higher DLL1 levels than patients with inflammatory diseases. Diagnostic performance was evaluated and showed better performance for DLL1 for the recognition of sepsis (AUC: 0.823; CI 0.731-0.914) than C-reactive protein (AUC 0.758; CI 0.658-0.857), PCT (AUC 0.593; CI 0.474-0.711) and White Blood Cell count (AUC 0.577; CI 0.46-0.694). DLL1 demonstrated promising results for diagnosing sepsis and was able to differentiate sepsis from other infectious and inflammatory diseases.